Fishing during the “new normality”: social and economic changes in galapagos small-scale fisheries due to the covid-19 pandemic - Viteri Mejía C., Rodríguez G., Tanner MK., Ramírez-González J., Moity N., Andrade S., Barragán Paladines M., Cáceres R., Castrejón M.; Pittman J. (My University, 2022)
The crisis caused by COVID-19 has profoundly affected human activities around the globe, and the Galapagos Islands are no exception. The impacts on this archipelago include the impairment of tourism and the loss of linkages with the Ecuadorian mainland, which has greatly impacted the local economy. The collapse of the local economy jeopardized livelihoods and food security, given that many impacts affected the food supply chain. During the crisis, the artisanal fishers of the Galapagos showed a high capacity to adapt to the diminishing demand for fish caused by the drastic drop in tourism. We observed that fishers developed strategies and initiatives by shifting roles, from being mainly tourism-oriented providers to becoming local-household food suppliers. This new role of fishers has triggered an important shift in the perception of fishers and fisheries in Galapagos by the local community. The community shifted from perceiving fisheries as a sector opposed to conservation and in conflict with the tourism sector to perceiving fisheries as the protagonist sector, which was securing fresh, high-quality protein for the human community. This study explores the socio-economic impacts and adaptations of COVID-19 on Galapagos' artisanal fisheries based on a mixed methods approach, including the analysis of fisheries datasets, interviews, surveys, and participant observation conducted during and after the lockdown. We illustrate the adaptive mechanisms developed by the sector and explore the changes, including societal perceptions regarding small-scale fisheries in the Galapagos. The research proposes strategies to enhance the Galapagos' economic recovery based on behaviors and traits shown by fishers which are considered potential assets to build-up resilience.
Keywords: Small-scale fisheries; Value chain; Adaptation mechanisms; Economic recovery; COVID-19; Galapago